Eating Disorders and Sedentary Behavior with Obesity Risk in Adolescents - Adyani, Sang Ayu Made; Purwandani, Ervina Ria (Poltekkes Kemenkes Gorontalo, 2025)
ABSTRACT Background: The incidence of obesity in adolescents continues to increase every year. Obesity is an overweight condition that exceeds normal limits due to the accumulation of fat in the body which can have an impact on physical health. This is a risk factor for causing death from non-communicable diseases. Adolescents who are obese in adolescence will continue into adulthood.Purpose: This study aims to determine the relationship of eating disorder and sedentary behavior with the risk of obesity in adolescents at SMAN 99 Jakarta.Methods: This study used a quantitative analytic survey method with a cross sectional design. The sample is 247 respondents with stratified random sampling technique. Data were collected using the Eating Attitudes Test (EAT-26) and Adolescent Sedentary Activity Questionnaire (ASAQ) questionnaires, as well as direct measurements of body weight and height.Results: The results of this study found that the majority of respondents were at risk of obesity with 192 (91.9%) respondents not experiencing eating disorders, while those who experienced eating disorders were 36 (94.7%) respondents. In addition, the majority of obese respondents who behaved sedentary were 120 (96.8%) respondents, while those who did not behave sedentary were 108 (87.9%) respondents.Conclusion: There is no association between eating disorder and the risk of obesity with a p-value of 0.541 (p>0.05), and there is an association between sedentary behavior and the risk of obesity with a p-value of 0.008 (p<0.05) in adolescents at SMAN 99 Jakarta.